Oxidative and Nitrosative Stress in Major Depressive Disorder: A Case Control Study - Aditya Somani; Abhishek Kumar Singh; Bandna Gupta; Sheela Nagarkoti; Pronob Kumar Dalal; Madhu Dikshit (Brain Sciences, 2022)
Introduction: The role of increased oxidative stress and alterations to the nitric oxide (NO) pathway have been implicated in major depressive disorder (MDD). The two pathways interact closely with each other but have not been studied simultaneously in MDD. This study aimed to assess and compare the levels of oxidative and nitrosative stress in the neutrophils (PMNs) of drug-naive MDD patients and their first-degree relatives. Methods: 29 drug-naive MDD patients and 27 healthy first-degree relatives and healthy controls aged 18–45 years were included in this study. An assessment of the levels of reactive oxygen species (ROS), nitrites, neuronal NO synthase (nNOS), and myeloperoxidase in PMNs, and cortisol in serum was carried out. Results: Compared to healthy controls, the generation of free radicals, myeloperoxidase activity, and nNOS mRNA expression in PMNs, and cortisol level in serum were significantly higher in drug-naive depression patients. Indeed, increased levels of myeloperoxidase and serum cortisol were also noted in first-degree relatives. The total nitrite content in the PMNs and plasma however was significantly lower in both patients and first-degree relatives. Interestingly, a positive correlation was established in the ROS levels in the PMNs, plasma and neutrophil nitrite, and the serum cortisol level between MDD patients and their first-degree relatives. Conclusion: The results of this study contribute towards a better understanding of the familial association of depressive disorder, and demonstrate for the first time that neutrophil ROS/RNS, plasma nitrite, and serum cortisol levels are positively correlated between MDD patients and their first-degree relatives. However, further studies in larger, more diverse samples are needed to extend these pathways as potential biomarkers to identify persons at high risk for psychopathology at an early stage.